Two decades of nonfatal injury data: a scoping review of the National Electronic Injury Surveillance System-All Injury Program, 2001-2021 - Livia Navon; Li Hui Chen; Mary Cowhig; Amy Funk Wolkin (BMC, 2023)
Abstract Background Injury is a leading cause of preventable morbidity and mortality in the USA. Ongoing surveillance is needed to understand changing injury patterns to effectively target prevention efforts. Launched jointly in 2000 by the Consumer Product Safety Commission (CPSC) and the Centers for Disease Control and Prevention (CDC), the National Electronic Injury Surveillance System-All Injury Program (NEISS-AIP) provides national-level estimates of US emergency department visits for nonfatal injuries. A scoping review of peer-reviewed articles was conducted to characterize how NEISS-AIP data have been used for injury surveillance in the USA. Main Body This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Three bibliographic databases (PubMed, Scopus, and Google Scholar) were systematically searched for English language peer-reviewed articles that used NEISS-AIP data as the primary data source during 2001-2021. Key article characteristics from included articles were abstracted to generate descriptive summary statistics to understand the use and limitations of NEISS-AIP for injury surveillance. Database queries returned 6944 citations; 594 citations were manually reviewed, and 167 non-duplicate journal articles were identified. An average of 8.0 articles (range: 1-14) were published annually during 2001-2021. Articles appeared in 72 different journals representing a diverse audience with the majority of articles written by CDC authors. Starting in 2013, a higher proportion of articles were published by non-CDC authors. The largest number of articles examined injury among all age groups (n = 71); however, the pediatric population was the specific age group of greatest interest (n = 48), followed by older adults (n = 23). Falls (n = 20) and motor-vehicle-related injuries (n = 10) were the most studied injury mechanisms. The most commonly identified limitation identified by authors of reviewed articles was that NEISS-AIP only produces national estimates and therefore, cannot be used for state- or county-level injury surveillance (n = 38). Conclusions NEISS-AIP has contributed to nonfatal injury surveillance in the USA. CDC and CPSC continue to work together to expand and enhance NEISS-AIP data collection. Researchers are encouraged to continue using this publicly available dataset for injury surveillance.